PERBEDAAN HASIL BELAJAR SISWA KELAS III SDIT NGANJUKMENGGUNAKAN MEDIA NYATA DAN MEDIA GAMBAR PADA PEMBELAJARAN DENGAN METODE EKSPERIMEN - Nita Wahyuningtiyas; Sulistiono Sulistiono (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
To improve student learning outcomes is the selection of methods and media appropriate learning. This study aims to determine the differences in learning outcomes with the experimental method supported the real media and experimental methods with the pictures media on the  third-grade students of SDIT Pace Nganjuk . Research conducted by experiments with subjects of the IIIA grade by 25 students taught by the experimental method supported of the real media  and the IIIB grade  by 25 students taught by the experimental method supported of the picture media. The results show that the average and mastery of cognitive learning outcomes of students who are taught by an experimental method supported of the real media are 81.00 and 100 % respectively better than those taught using the experimental method supported of the picture media are 76.75 and 85 % respectively . Average affective and psychomotor learning outcomes of students who are taught by an experimental method supported of the real media are 13.85 and 12 respectively , while the average affective and psychomotor learning outcomes of students who are taught by an experimental method supported of the picture media  are 11 and 10.5 respectively. Keywords: experimental methods, real media, picture, learning outcomes